ANALISIS BEBAN KERJA DALAM PENENTUAN KEBUTUHAN PEKERJA YANG OPTIMAL DENGAN MENGGUNAKAN METODE FTE DAN WLA (Studi kasus: PT. Kunango Jantan) - Nur, Muhammad; Adilla Frenita, Zurids (SPECTA Journal of Technology, 2024)
Human resources are part of company assets that need to be managed well because they have a big influence on company performance. Tower division PT. Kunango Jantan is a business group engaged in the manufacture and strengthening of towers. Workers in the tower division are currently not fully structured well because there are still workers who have more than one position, which makes the workload felt by workers high and can disrupt worker productivity. So research is needed to idetermine the workloadi received by each worker using the Full Time iEquivalent (FTE) and Workload Analysis (WLA) methods. In this research, using the FTE method, it was found that there wasi an imbalance in the workload of each tower division worker in the overload category. For this reason, the company makes improvements by paying more attention to the capabilities and work facilities of each worker and can add additional workers. Using the WLA method, the optimal number of workers is 28 out of the actual 13 workers in the tower division.